2019
DOI: 10.1136/bcr-2019-232000
|View full text |Cite
|
Sign up to set email alerts
|

Chryseobacteriumspp-associated bacteraemia in a haemodialysis patient: a diagnostic challenge

Abstract: Chryseobacterium species are Gram-negative bacillus widely distributed in nature. It is a rare human pathogen that has been isolated from water systems and humid surfaces of the hospital environment. We report a rare case of Chryseobacterium bacteremia in an end-stage renal disease nursing home resident, that was diagnosed using multiplex PCR and was successfully treated with intravenous piperacillin–tazobactam combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…This nosocomial acquisition of Chryseobacterium bacteremia can be attributed to its property to colonize and form biofilms on humid medical devices like a humidifier, respirators, contaminated catheters and surgical instruments and spread in a hospital setting through contaminated medical devices [18]. The above finding was consolidated by a study from North India that reported a history of indwelling medical devices in 55.56 % (10/18, 55.56 %) of their patients [19,23,24]. [18].…”
Section: Discussionmentioning
confidence: 99%
“…This nosocomial acquisition of Chryseobacterium bacteremia can be attributed to its property to colonize and form biofilms on humid medical devices like a humidifier, respirators, contaminated catheters and surgical instruments and spread in a hospital setting through contaminated medical devices [18]. The above finding was consolidated by a study from North India that reported a history of indwelling medical devices in 55.56 % (10/18, 55.56 %) of their patients [19,23,24]. [18].…”
Section: Discussionmentioning
confidence: 99%